2019
DOI: 10.1152/ajpregu.00088.2019
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent impairments to cerebral vascular reactivity with type 2 diabetes mellitus in the Goto-Kakizaki rat

Abstract: Type 2 diabetes mellitus (T2DM) is a prevalent pathology associated with elevated cerebrovascular disease risk. We determined wall mechanics and vascular reactivity in ex vivo middle cerebral arteries (MCA) from male Goto-Kakizaki rats (GK; ~17 wk old) versus control Wistar Kyoto rats (WKY) to test the hypothesis that the diabetic environment in GK, in the absence of obesity and other comorbidities, leads to endothelial dysfunction and impaired vascular tone regulation. Dilation of MCA following challenge with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Previous studies in humans have shown positive correlation between circulating irisin levels and endothelium-dependent vasodilation [ 12 ], flow-mediated dilation [ 24 ], and coronary atherosclerosis index [ 30 ], suggesting irisin may regulate vascular endothelial function. Metabolic dysfunction such as obesity and T2D is associated with endothelial dysfunction characterized by impaired endothelium-dependent vasorelaxation in the experimental rodent models and in humans [ 12 , 40 , 41 , 42 , 43 , 44 ]. Although exogenous irisin has been suggested to increase energy expenditure and reduce high fat diet-induced obesity and insulin resistance [ 1 ], it is still unclear whether exogenous irisin administration ameliorates vascular dysfunction which is induced by abnormal metabolism, and whether irisin may induce vasoconstriction or vasodilation in the vasculature.…”
Section: The Potential Role Of Irisin In Vascular Reactivity and Amentioning
confidence: 99%
“…Previous studies in humans have shown positive correlation between circulating irisin levels and endothelium-dependent vasodilation [ 12 ], flow-mediated dilation [ 24 ], and coronary atherosclerosis index [ 30 ], suggesting irisin may regulate vascular endothelial function. Metabolic dysfunction such as obesity and T2D is associated with endothelial dysfunction characterized by impaired endothelium-dependent vasorelaxation in the experimental rodent models and in humans [ 12 , 40 , 41 , 42 , 43 , 44 ]. Although exogenous irisin has been suggested to increase energy expenditure and reduce high fat diet-induced obesity and insulin resistance [ 1 ], it is still unclear whether exogenous irisin administration ameliorates vascular dysfunction which is induced by abnormal metabolism, and whether irisin may induce vasoconstriction or vasodilation in the vasculature.…”
Section: The Potential Role Of Irisin In Vascular Reactivity and Amentioning
confidence: 99%
“…In skeletal muscle, dilation from mild hypoxia (15% O 2 ) was mostly NO-dependent, while moderate (10% O 2 ) was mediated by a combination of increased PGI 2 and decreased 20-HETE, and severe (0% O 2 ) was almost entirely accounted for by an increase in PGI 2 [141]. In all cases, there appears to be significant involvement by the endothelium to mediate the dilation, which is further supported by a reduction in hypoxic dilation when isolated vessels were exposed to indomethacin (an inhibitor of AA metabolism and thus the production of PGI 2 ) [137,144,145] and to a lesser degree by L-NAME (an inhibitor of NO production from NOS) [145]. Therefore, PGI 2 is likely a substantial contributor to hypoxic dilation with a lesser but likely still significant role for NO.…”
Section: Pomentioning
confidence: 88%
“…The chronic inflammatory state seen in MetS likely contributes to the reduction in NO bioavailability due to increased scavenging to the produced NO by reactive oxygen species since this reduction in NO bioavailability is consistently reported to evolve in parallel with oxidant stress and the development of a chronic inflammatory state [185,186]. This is supported by improved dilatory reactivity of MCA with the pretreatment of the cell-permeable superoxide dismutase mimetic TEMPOL in a model of T2DM [145]. Interestingly some studies have actually shown an increase in eNOS expression which may be an attempt to compensate for the increased scavenging; however, they too continue to find reduced dilator reactivity [187].…”
Section: Effect Of Diseased Statesmentioning
confidence: 97%
See 2 more Smart Citations